Privatisation of Tradeable Government Information - Guha, B. (DESIDOC Journal of Library & Information Technology, 2002)
The author discusses the concept of tradable information and the methods of value addition to the government held information and the possibilities of privatisation in this area. It also mentions the outcome of the first information industry-promoter-user meet held by NISSAT in 1994 and the subsequent work that is required to be done in this area. http://dx.doi.org/10.14429/dbit.15.5.3197